2022
DOI: 10.7759/cureus.23562
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: A Curious Abettor in the Occurrence of Stevens-Johnson Syndrome

Abstract: Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are immune-mediated life-threatening skin diseases. The condition is known to be caused by various infections, drugs (mainly antibiotics), or can be idiopathic. Amidst the novel coronavirus 2019 (COVID-19) pandemic, there is an increasing number of SJS/TEN cases being reported. Viral infections are known to have decreased the threshold of drug reactions by inducing a pro-inflammatory state in the body. We report a case of TEN secondary to tams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…et al have reported a case of toxic epidermolysis associated with tamsulosin after COVID-19 [3]. This case would add to the list of possible adverse effects of posaconazole and would help internists to consider the renal adverse effects of posaconazole.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…et al have reported a case of toxic epidermolysis associated with tamsulosin after COVID-19 [3]. This case would add to the list of possible adverse effects of posaconazole and would help internists to consider the renal adverse effects of posaconazole.…”
Section: Discussionmentioning
confidence: 92%
“…These are either due to direct infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), immune modulation by the virus, or due to the drugs used to treat COVID-19. Viral infections have been reported to induce a pro-inflammatory state in the body which predisposes the patient to a variety of previously unreported adverse reactions to medications [3]. Apart from the immune modulation by SARS-CoV-2, steroids, tocilizumab, and other immunosuppressants used for the treatment of COVID-19 contributed to the emergence of opportunistic infections such as mucormycosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…and herpes simplex viruses. Human herpes virus (HHV)-6 (1), Epstein-Barr virus (EBV) (2), Mycoplasma pneumoniae (3)(4)(5), and novel coronavirus infection (6,7) are associated with the occurrence and progression of SJS/ TEN. M. pneumoniae and novel coronaviruses can directly cause SJS/TEN.…”
Section: Introductionmentioning
confidence: 99%
“…El SSJ es una dermatosis reactiva, desencadenada por una reacción tardía de hipersensibilidad, mediada por complejos inmunes; se presenta como un eritema multiforme vesiculobulloso, con compromiso de mucosas y síntomas sistémicos, inducido por fármacos más frecuentemente, con algunos casos relacionados a procesos infecciosos y en ocasiones idiopático, con una alta tasa de mortalidad (Ochani, R Et al 2021) (Oakley, A. And Krishnamurthy, K. 2022) (Grover, D Et Al 2022).…”
Section: Introductionunclassified